Differential effects of baclofen and oxytocin on the increased ethanol consumption following chronic psychosocial stress in mice. (6th November 2012) - Peters, Sebastian; Slattery, David A.; Flor, Peter J.; Neumann, Inga D.; Reber, Stefan O.
Abstract Chronic stress is known to enhance the susceptibility for addiction disorders including alcoholism. While these findings have been recapitulated in animal models, the majority of these studies have utilized non‐social rather than social stress paradigms; the latter of which are believed to be more relevant to the human situation. Therefore, the major aim of this study was to investigate, if 14 days of chronic subordinate colony housing (CSC), a pre‐clinically validated psychosocial stress paradigm relevant for human psychiatric and somatic disorders, enhances ethanol (EtOH) consumption in male mice. To assess this, we employed the well‐established two‐bottle free‐choice paradigm where mice were given access to water and 2, 4, 6 and 8% EtOH solutions (with the concentrations increasing each fourth day) following termination of the stress procedure. After 14 days of CSC, stressed mice consumed significantly more EtOH at all concentrations tested and displayed increased EtOH preference at concentrations of 6 and 8%. This effect was not due to an altered taste preference in CSC mice as assessed by saccharine‐ and quinine‐preference tests, but was accompanied by increased anxiety‐related behavior. Systemic administration of baclofen (2.5 mg/kg) or oxytocin (OXT; 10 mg/kg) reduced the EtOH intake in single housed control (baclofen, OXT) and CSC (baclofen) mice, whereas intracerebroventricular OXT (0.5 μg/2 μl) was ineffective in both groups. Taken together, these results suggest that (i) chronic psychosocial stress enhances EtOH consumption, and (ii) baclofen and OXT differentially affect EtOH intake in mice.